Political Communication In South Africa After Rubicon - Paul Vorster (Communicare)
As voters have become used to the sophisticated presentation of messages in other spheres, they expect a similar sophistication in political communication. This has opened the way for political adver- tising In addition to traditional modes of political communication. This paper ex- amines political advertising in South Africa. It looks at political advertising In the Referendum '83 campaign, the communica- tlons disaster generally known as Rubicon and the new approach for Rubicon II. It proposes the utilisation of professionals in the communications field to assist in the formulation of a national communications policy to promote more open and more ef- fective government communication.